Ranking of planting composition attributes in campus well-being / Norizan Mt Akhir ... [et al.] - Mt Akhir, Norizan; Md Sakip, Siti Rasidah; Abbas, Mohamed Yusoff; Othman, Noriah (2021)
Planting composition is the art of arranging individual plants using similar or different species with a distinctive element of size, colour, texture or form. These composition attributes may influence viewers’ preferences. Theoretically, people always respond to beautiful and well-planted surroundings rather than mysterious and complicated planting design. The research aims to rank the planting composition attributes which are able to enhance the campus environment and community well-being. Therefore, the collection of planting composition images are grouped accordingly, and the mean results recorded to achieve the aim of attributes ranking objectively. The descriptive analysis was used as a method to quantify the mean results. The ranking is significant to determine the quality of green needed by the community on campus for their life and well-being. As a result, the research findings are able to guide the designers to sensibly setting the planting design, particularly in the campus environment.